2015
DOI: 10.1159/000430164
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Recurrence of Giant Cell Tumor of Bone After Surgery: A Clinicopathological Study of 80 Cases from a Single Center

Abstract: Background/Aims: This aim of the present study was to identify specific markers determining the recurrence of the giant cell tumor of bone (GCTB). Methods: This study involved the clinicopathological analysis of 80 cases. All of the clinical features, pathological fracture, Campanacci grade, histological features and surgical methods were reviewed. Immunohistochemistry was used to detect the expression of Ki-67, CD147, mutant p53 and p63 in GCTB. Comparisons between different groups were performed using the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
1
31
1
Order By: Relevance
“…DFS was considered the interval between the date of UTUC surgery and the time of appearance of the first locoregional recurrence or distant metastasis. CSS was defined as the interval between the date of UTUC surgery and the time of UTUC-related death [27]. The potential prognostic factors were established by univariate analysis, and only the significant factors were entered into multivariate Cox proportional hazard regression models.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…DFS was considered the interval between the date of UTUC surgery and the time of appearance of the first locoregional recurrence or distant metastasis. CSS was defined as the interval between the date of UTUC surgery and the time of UTUC-related death [27]. The potential prognostic factors were established by univariate analysis, and only the significant factors were entered into multivariate Cox proportional hazard regression models.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Based on the Campanacci classification, which has been widely accepted in evaluating giant cell tumor, grade III represented the aggressive type. A series of studies reported Campanacci grade III as the risk factor for tumor recurrence [19,20] and lung metastasis [21,22]. The recurrence was also reported to be a risk factor for resulting in metastasis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The term "malignancy in GCTB" is used by the World Health Organization to describe such tumors, which show malignant potential and can completely transform into malignant tumors [25,26]. Currently, preoperative prediction and postoperative monitoring of GCTB patient prognosis are limited and mostly rely on patients' general information, radiological features, treatment history, and tumor pathological reports [1,4,5]. Therefore, identification of sensitive and specific factors that can predict tumor progression and prognosis, particularly those found in the serum, are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…GCTB predominantly occurs in the metaphysis, thoracic vertebra, and sacrum of individuals in their third and fourth decades of life and shows a female predilection [1,[3][4][5]. This kind of tumor is osteolytic and comprises three major cell populations: osteoclast-like multinuclear giant cells, mononuclear precursors of osteoclasts, and spindle-shaped stromal cells (GCTSCs) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%